Strategies in Improving the Quality of Education that is Superior & Competitive - Altaf Syauqy Iqbal Saifani; Andriyani; Suhana binti Sarkaw; Andry Priharta (CV. Creative Tugu Pena, 2025)
Enhancing the quality of education to achieve excellence and competitiveness is a top priority in the development of the national education system. This study employs a literature-based research method to explore key strategies for improving educational quality. The findings indicate that essential strategies include developing a competency-based curriculum, enhancing the quality of teaching staff, strengthening educational infrastructure, adopting modern learning technologies, and fostering collaboration between educational institutions and industry. Furthermore, the establishment of an academic culture that promotes innovation and creativity, along with the implementation of a rigorous quality assurance system, are critical factors in achieving sustainable improvement. In conclusion, improving the quality of education requires a holistic and sustainable approach involving all stakeholders in the educational ecosystem. This study contributes to the field of educational development by synthesizing key strategic elements that can serve as a practical framework for policymakers, educators, and institutional leaders in designing and implementing initiatives to enhance educational quality and competitiveness.